(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Fourteen genotypes of Lablab bean were studied for sixteen yield and yield contributing characters. The experiment was conducted at Field Laboratory of Department of Genetics and Plant Breeding, Bangladesh Agricultural University, Mymensingh. Seed yield per plant showed positive and significant correlation with days to maturity, number of raceme per plant, raceme length, pod length, green pod yield per plant, green test weight and shelling percentage and significant negative correlation with days to maturity, number of seeds per pod and protein content at both phenotypic and genotypic levels. Path analysis revealed that green pod length exhibited high positive direct effect on number of raceme per plant, raceme length, green pod width, dry test weight and shelling percentage. The direct negative effects on seed yield were observed by days to maturity, number of flower buds per raceme, green pod yield per plant, green test weight and protein content and revealed the importance of these traits for simultaneous selection of plant for yield improvement.